The Prophetic Methods in Activating the Civilizational Values in the Islamic World: The Values of Knowledge, Perfection, and Time Management as a Model - ALghonmeen, Osama Adnan Eid; Baaliousaid, Khoudir (Dirasat: Shari’a and Law Sciences, 2020)
This research seeks to reveal the importance of values ​​in advancing civilization by focusing on the role of some important behavioral and skill values, starting from the life of Prophet Muhammad - may God’s prayers and peace be upon him. The study focused on four important values: knowledge, mastery, diligence, and time management. By reviewing how the Prophet, may God bless him and grant him peace, instilled these values in Muslims. Then the study clarifies the effect of these values on the advancement of society from various aspects. The study adopted the analytical approach by studying the texts that focused on this topic and trying to understand them and the methods of their activation; to benefit from the development of contemporary reality. The research concluded that these values ​​are of great importance in organizing society, improving cultural and living standards, liberating Muslims from political and economic dependence, and giving a good image of Islam. The study also extracted from the Prophetic Sunnah methods of embodying and consolidating these values ​​in contemporary societies. The study recommends the need to use media platforms and educational curricula to support values by teaching them in schools with practical attitudes and using various media platforms to emphasize their importance.